2016
DOI: 10.1111/josh.12395
|View full text |Cite
|
Sign up to set email alerts
|

Active Travel to School: Findings From the Survey of US Health Behavior in School‐Aged Children, 2009‐2010

Abstract: Although ATS is low among US children, significant variation exists. HBSC is a promising data source for an ATS study. As the first study to explore the variation of ATS at school level, this research contributes uniquely to current knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Active transport to school was less common in the nationally distributed sample (around 25%). This is consistent with Yang and colleagues , but somewhat higher than other reports and much lower than reports from other countries . Clearly, this level of participation affords room for improvement, and current efforts are underway to increase active transport to school .…”
Section: Discussionsupporting
confidence: 89%
“…Active transport to school was less common in the nationally distributed sample (around 25%). This is consistent with Yang and colleagues , but somewhat higher than other reports and much lower than reports from other countries . Clearly, this level of participation affords room for improvement, and current efforts are underway to increase active transport to school .…”
Section: Discussionsupporting
confidence: 89%
“…This contradiction may be indicative of the many cultural differences related to automobile use and active transportation between the U.K. and the U.S. For example, a 2014 travel survey revealed that 46% of 5 to 10 year olds in the U.K. walk to school (U.K. Department for Transport, 2014), compared to an estimated 21.4% in the U.S. (Yang et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…For example, factors such as neighborhoods far from the destination, disconnected streets, changes in the built environment and a lack of public safety are associated to lower ATS 14 . Moreover, differences by gender are prevalent in the literature on ATS 15,16 . The results indicate that boys are more likely to use ATS than girls 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, differences by gender are prevalent in the literature on ATS 15,16 . The results indicate that boys are more likely to use ATS than girls 16 . The publication of these data may contribute to planning policies and programs that consider the regional characteristics of active transportation, as well as strategies to promote these practices.…”
Section: Introductionmentioning
confidence: 99%